Pengembangan Taman Kota Sebagai Ruang Ketiga (Third Place) Di Kota Banda Aceh - Syifaurrahmah Syifaurrahmah; Sylvia Agustina; Myna Agustina Yusuf (PT Riset Mandiri Nusantara, 2025)
Rapid urban growth and population increases in Banda Aceh have heightened the need for public spaces that support community interaction. City parks have emerged as potential